ANALISIS TREN PENCARIAN INFORMASI: KASUS KEDAI KOPI RAMU - Linda Ramadhanti; Sri Fatimah (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
The Ramu Coffee Shop is thought to have experienced a shift in function, now the coffee shop has become a place for socialization and information-seeking media. The sales of Ramu Coffee Shops are still fluctuating and even tend to decline, even though coffee consumption in Indonesia has continued to increase in the last five years. In order to increase sales, Kopi Ramu advertises on Instagram social media using the Instagram Ads feature, but it is not yet known to what extent its effectiveness. The study aims to describe the characteristics and information-seeking behavior of Kopi Ramu's followers, as well as the effectiveness of Kopi Ramu product advertisements on Instagram social media. The research method used is descriptive analysis and average score. The results showed that the followers of Kopi Ramu Instagram were dominated by students aged 20-25 years, not limited to a certain gender, and the latest education was a high school graduate or equivalent with an income of less than Rp. 1,000,000. Kopi Ramu advertisements displayed on instagram social media are in the "Effective" category with an average score of 4.05. Information seeking behavior at the Ramu Coffee Shop is "Positive" with an average score of 3.697.